Mothering Sunday [videorecording (DVD)] - Birch, Alice, 1986-; Young, Odessa, 1990-; O'Connor, Josh; Dirisu, Sope, 1991-; Ferran, Patsy; D'Arcy, Emma, 1992-; Jackson, Glenda; Colman, Olivia; Firth, Colin, 1960-; Swift, Graham, 1949- (Sony Pictures Home Entertainment, 2022)
With her employers out, a maid in 1920s England has a rare chance to meet with her secret lover, the son from a nearby manor. Class issues keep them apart, and although he is about to leave to marry a suitable wife, the events of this weekend could change their lives -- and love -- forever.